2013
DOI: 10.1016/b978-0-12-394587-7.00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Oligomerization and Allostery

Abstract: Oligomerization of chemokine receptors has been reported to influence many aspects of receptor function through allosteric communication between receptor protomers. Allosteric interactions within chemokine receptor hetero-oligomers have been shown to cause negative cooperativity in the binding of chemokines and to inhibit receptor activation in the case of some receptor pairs. Other receptor pairs can cause enhanced signaling and even activate entirely new, hetero-oligomer-specific signaling complexes and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 129 publications
(162 reference statements)
3
55
0
Order By: Relevance
“…Heterodimerization of this receptor with the ghrelin receptor (GHSR1a) has been shown to impede GHSR activity [43]. The dimerization across the various CXCR4 crystal structures is consistent with reports of CXCR4 homo- and heterodimerization in cells and its possible physiological relevance [44]. These and many other studies have confirmed that dimerization and / or oligomerization play important roles in receptor function.…”
Section: Introductionsupporting
confidence: 71%
“…Heterodimerization of this receptor with the ghrelin receptor (GHSR1a) has been shown to impede GHSR activity [43]. The dimerization across the various CXCR4 crystal structures is consistent with reports of CXCR4 homo- and heterodimerization in cells and its possible physiological relevance [44]. These and many other studies have confirmed that dimerization and / or oligomerization play important roles in receptor function.…”
Section: Introductionsupporting
confidence: 71%
“…Finally, our data do not exclude the possibility that receptor oligomerization contributes to other processes, such as regulation of pharmacology and trafficking of homo-versus heterooligomers (82,83). It may also contribute to the coordination and efficiency of sequential steps in the GPCR lifecycle.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have suggested that GPCR oligomerization may account for the formation of multiprotein complexes at the cytoplasmic surfaces of the receptors (27,65,66), and indeed, many chemokine receptors have been shown to homo-and hetero-oligomerize in cells (67)(68)(69). Furthermore, five crystal structures of CXCR4 from different space groups all revealed similar dimers (70).…”
Section: -mentioning
confidence: 88%